Kebijakan Pemerintah Dalam Rangka Pemulihan Ekonomi Dan Keterkaitannya Dengan Merebaknya Flu Burung - Muryani, Muryani (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 2, Agustus 2015 (pp. 113-216)DO - 10.24843/JEKT.2015.v08.i02.p10, 2015)
The negative impact of the outbreak of bird flu on economic sectors in the sectoral and macro aspect is analized using Computable General Equilibrium (CGE) models. Base on SNSE 2008 dataand some disagregation data sectors, two simulations are conducted. The result of the simulation studies indicate that there is the decrease in the production of poultry meat sector (traditional and medium-large) and egg sectors impact on the micro and macro aspects of the economy. This research is the second step of my research deal with Avian flu and the economy.The first step was the negative impact of avian flu on economy which was already published on Asian Social Economic Journal by last year. The result of this research are : On the micro level in domestic market there are decresed production and increased prices in the poultry sector, eggs, other farms, restaurants and services. While in the foreign market there are decresed exports as well as imports. Similarly, there is a decline in consumption by the entire group of household due to a decline in the acceptance by all groups of households and firms. Government revenue also declined due to a decrease in taxes from households and firms.At the macro level there are a decline in GDP and a decline in the investment. The last  simulation illustrate  the increase of production and the impact of government policy on the micro aspects and the overall economy.  On the micro level in domestic market there are increased production and falling prices in the sector of poultry, eggs, other farms, restaurants and services. While in foreign market there are  increased exports and  decreased imports in almost all sectors. Similarly, there are an increase in consumption by the entire group of households due to an increse in the acceptance by all groups of households and firms. Government revenue also increased due to an increse in taxes from household and firms.
Keywords: avian influenza, policy, impact, economy.